Rubus inopertus var. echinocalyx, R. pentagonus var. eglandulosus and Spiraea japonica var. pinnatifida, three synonyms of Rosaceae - Xiong, Xian-Hua; Liu, Chao; Pu, Yu-Qing; Liu, Mei (Phytotaxa, 2025)
On the basis of studies of protologues, examination of type and herbarium specimens, and field observations, three names in Rosaceae, Rubus inopertus var. echinocalyx, R. pentagonus var. eglandulosus and Spiraea japonica var. pinnatifida, are treated as synonyms of R. inopertus var. inoperatus, R. quinquefoliolatus and S. micrantha var. micrantha respectively.